Inflammatory Cytokines Changed in Patients With Depression Before and After Repetitive Transcranial Magnetic Stimulation Treatment - Wang, Qiang; Zeng, Lingyun; Hong, Wenjuan; Luo, Mingying; Zhao, Nan; Hu, Xiaofen; Shi, Meili; Qiu, Jing; Shen, Yanmin; Teng, Xiuju; Min, Haiying; Liu, Weiqing (Frontiers in Psychiatry, 2022)
Studies have found that repetitive transcranial magnetic stimulation rTMS can produce antidepressant effects by affecting inflammatory cytokines in patients with depression, which plays a key role in the therapeutic mechanism of antidepressants. This study aimed to explore the changes in inflammatory cytokine levels in patients with depression after 4 weeks of rTMS treatment to determine the possible antidepressant mechanism of rTMS. This prospective, double-blind, pseudo-stimulus-controlled study was conducted, and a total of 57 patients with depression and 30 healthy controls were recruited. Patients were randomly divided into the active rTMS (n = 29) and sham rTMS groups (n = 28). The Hamilton Depression Scale was used to evaluate depressive symptoms and their severity. The serum levels of seven inflammatory cytokines were measured using enzyme-linked immunosorbent assay. Inflammatory cytokines include high-sensitivity C-reactive protein (CRP-hc); tumor necrosis factor (TNF-α); interferon (IFN-γ); interleukin-2 (IL-2); interleukin-4 (IL-4); interleukin-6 (IL-6); and interleukin-8 (IL-8). At baseline, TNF-α (F = 36.699, p < 0.001), IFN-γ (F = 8.907, p < 0.001), IL-4 (F = 66.256, p < 0.001), and IL-2 (F = 9.162, p < 0.001) levels in the depression group were significantly different from those of healthy controls. In the self-control analysis of the active rTMS group, the levels of IL-2 and CRP-hc increased significantly after 2 and 12 weeks of treatment. In the sham-rTMS group, IFN-γ increased after 2 and 12 weeks of treatment. Our results revealed that the changes in inflammatory cytokines after rTMS treatment showed different patterns compared to the sham group, suggesting that the antidepressant effect of rTMS may be related to changes in inflammatory cytokines.